Literary references to the dirham and the dinar in the mudéjar-morisco Manuscript of Ocaña - Hofman Vannus, Iris (Anaquel de Estudios Árabes, 2004)
The following essay deals with the references to the dirham and the dīnār, which are found in the Mudéjar-Morisco Manuscript of Ocaña (Toledo, Spain). Hidden in a closet in a wall of the Casa de la Encomienda in Ocaña in 1969, this manuscript is anonimous and without date, though the datation can be established in the second half of the XVth century. It is a small muslim breviary (10x 7 cm), of one hundred and eighty eight folios, written on both sides in magrebī letters. In spite of its antiqueness, it is in good shape. We have extracted of the Manuscript the references to the dirham and to the dīnār, the most representative coins of the islamic monetary system, in order to show their use in a literary text of religious teaching and in order to indicate their referencial validity in the vast muslim empire during all times.